Bound to you : includes Spellbound and See you later - Pike, Christopher, 1955- (New York : Simon Pulse, 2012)
Contains two novels including'Spellbound,' in which, Jason returns to the site of Karen's death with his new girlfriend and some friends from school, but tragedy strikes again and the group must discover what evil forces are lurking in Crystal Falls; and'See You Later,' in which, Mark has just fallen in love for the first time with Becky who already has a boyfriend, but then a strange couple offers to break the couple up.
Spellbound -- See you later
'These books were previously published individually.' -- T.p. verso.
Keywords: Interpersonal relations -- Fiction; Detective and mystery stories